2021
DOI: 10.1021/acs.est.1c01792
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Lethal Peak Exposure to Insecticides Triggers Olfaction-Mediated Avoidance in Zebrafish Larvae

Abstract: In agricultural areas, insecticides inevitably reach water bodies via leaching or run-off. While designed to be neurotoxic to insects, insecticides have adverse effects on a multitude of organisms due to the high conservation of the nervous system among phyla. To estimate the ecological effects of insecticides, it is important to investigate their impact on non-target organisms such as fish. Using zebrafish as the model, we investigated how different classes of insecticides influence fish behavior and uncovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…In order to do so, sample triplicates were analyzed on the first day and the last day of exposure. The detailed method is described by Könemann et al (2021) . Briefly, samples were separated using LC on a C18 Nucleodur column and measured using a Quadrupole Orbitrap mass spectrometer (Q Exactive Plus, Thermo Fisher Scientific Inc., USA) with electrospray ionization in a positive ion mode.…”
Section: Methodsmentioning
confidence: 99%
“…In order to do so, sample triplicates were analyzed on the first day and the last day of exposure. The detailed method is described by Könemann et al (2021) . Briefly, samples were separated using LC on a C18 Nucleodur column and measured using a Quadrupole Orbitrap mass spectrometer (Q Exactive Plus, Thermo Fisher Scientific Inc., USA) with electrospray ionization in a positive ion mode.…”
Section: Methodsmentioning
confidence: 99%
“…Cu-exposed zebrafish exhibited different microRNA (miRNA) expression profiles in a dose–response manner, and these deregulated miRNAs may be involved in neurogenesis . To date, numerous studies have confirmed the association between chemosensory dysfunction and environmental contaminants. However, the potential mechanisms underlying the effects of contaminants on the chemosensory process remain poorly understood …”
Section: Introductionmentioning
confidence: 99%
“… 20 To date, numerous studies have confirmed the association between chemosensory dysfunction and environmental contaminants. 21 23 However, the potential mechanisms underlying the effects of contaminants on the chemosensory process remain poorly understood. 15 …”
Section: Introductionmentioning
confidence: 99%
“…In juvenile Coho salmon, low levels of copper also increased the fish's vulnerability to predators, but via a different mechanism, namely by decreasing its ability to detect and respond to chemosensory cues indicating predator presence (McIntyre et al, 2012). Zebrafish larvae were shown to smell the presence of certain insecticides in water and actively avoid contaminated areas, raising the question of whether chemicals can affect fish migratory behaviour as a result (Könemann et al, 2021). Similar effects can be expected to unfold in other animal species as well.…”
Section: Multifaceted Ecological Impacts Of Chemicalsmentioning
confidence: 99%